Comportamento de Trichogramma pretiosum Riley (HYMENOPTERA: TRICHOGRAMMATIDAE) no manejo biológico de Spodoptera eridania (CRAMER) (LEPIDOPTERA: NOCTUIDAE), na cultura do tomateiro - Madalon, Fernando Zanotti. (2018)
Tomato is the most important fruit of the State of Espírito Santo, being cultivated in a huge area of this territory. Recently Spodoptera eridania (CRAMER) (Lepidoptera: Noctuidae) has been reported frequently in these crops, causing damages. In phytosani